EKSTRAKSI DAN ANALISIS FITOSTEROL LEMBAGA GANDUM (Triticum sp.) [Extraction and Analysis of Phytosterol from Wheat Germ (Triticum sp.)] - Sri Anna Marliyati; Hidayat Syarief; Deddy Muchtadi; Latifah K Darusman; Rimbawan Rimbawan (Jurnal Teknologi dan Industri Pangan, 2005)
Phytosterol may reduce the absorption of cholesterol, and used for preventing atherosclerosis. It is limited in soybean, but potentially abundant in wheat germ. Research on the utilization of wheat germ sterol had not been reported so far. Many aspects of germ sterol extraction from wheat germ and its characteristics were still unknown. In this research, the best extraction method, kinds and content of phytosterol from wheat germ were investigated. This research consisted of two steps: (1) extraction of phytosterol directly form whole germ and ground germ using hexane, and indirect extraction through germ oil using hexane and mixed solvent of hexane and ethanol, and direct extraction from ground germ using ethanol; (2) analysis of the type and content of phytosterol in the crude extract through the following steps: preparation of crude extract, fractionation, and analysis. Results showed that indirect extraction through germ oil was considered as the best method which yielded 1.37% of phytosterol. The highest yield was obtained when extracted using a mixed solvent of hexane Ã¢â‚¬â€œ ethanol 82:18. However, the odor of ethanol and hexane (gasoline like odor) was still detected. The solventÃ¢â‚¬â„¢s ratio of hexane to ethanol at 1:2 resulted better odor of the extract. Extraction of sterol using ethanol yielded 18.39% of sterol when the ratio of germ to ethanol at 1:10 (w/v) was applied. Results of quantitative analysis on the main component of crude extract of wheat germ sterol showed that the total content of sterol extracted with mixed solvent was higher than those extracted with ethanol. The ratio of hexane to ethanol at 1:1 (v/v) gave higher content of total sterol, stigmasterol and campesterol, whereas higher content of -sitosterol was produced at the solventÃ¢â‚¬â„¢s ratio of hexane to ethanol at 1:2 (v/v).